Frataxin Loss Promotes Angiotensin II–Induced Endothelial‐to‐Mesenchymal Transition - Yuetong Guo; Xingyi Cheng; Chenglin Huang; Jing Gao; Weili Shen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The metabolic flexibility of endothelial cells is linked to their phenotypic plasticity. Frataxin is critical in determining the iron metabolism and fate of endothelial cells. This study aimed to investigate frataxin‐mediated metabolic remodeling during the endothelial‐to‐mesenchymal transition (EndoMT). Methods and Results Endothelial cell‐specific frataxin knockout and frataxin mutation mice were subjected to angiotensin II to induce hypertension. EndoMT and cardiac fibrosis were assessed using histological and protein expression analyses. Fatty acid oxidation (FAO) in microvascular endothelial cells was measured using a Seahorse XF96 analyzer. We showed that inhibition of FAO accompanies angiotensin II‐induced EndoMT. Frataxin knockout mice promote EndoMT, associated with increased cardiac fibrosis following angiotensin II infusion. Angiotensin II reduces frataxin expression, which leads to mitochondrial iron overload and subsequent carbonylation of sirtuin 3. In turn, carbonylated sirtuin 3 contributes to the acetylated frataxin at lysine 189, making it more prone to degradation. The frataxin/sirtuin 3 feedback loop reduces hydroxyl‐CoA dehydrogenase α subunit–mediated FAO. Additionally, silymarin is a scavenger of free radicals, restoring angiotensin II–induced reduction of FAO activity and sirtuin 3 and frataxin expression, improving EndoMT both in vitro and in vivo. Furthermore, frataxin mutation mice showed suppressed EndoMT and improved cardiac fibrosis. Conclusions The frataxin/sirtuin 3 feedback loop has the potential to attenuate angiotensin II–induced EndoMT by improving FAO.